TELAAH SISTEM PENGENDALIAN MANAJEMEN DALAM FAMILY BUSINESS - Alfonsus Natanael; Andrea Secioria Dimitri; Muhammad Rifky Apriandi; Hanif Hanif (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
This study aims to examine the design of management control systems, in two business groups with different cultural backgrounds. The difference in cultural backgrounds is due to one of them from the company founders in the two companies who have different cultural life backgrounds, and in the end will be carried away by them in the formation of the organizational culture of each company. The research uses the literature study method by examining two research results, namely from the research of Efferin & Hartono (2015) on Management Control and leadership Styles in Family Business: An Indonesian Case Study and Hanif (2015) Management Control System Design: An Interpretive Ethnography. The results of the study strengthen the existence of contingency theory which states that companies will interact with their environment, with their ecosystems, and this will be seen in all aspects related to the management control system. The culture of society, in which the main actors from the founders to the managers of the company have lived, participate in coloring the organizational culture of the company, and in the end, in the design of the management control system.